Effects of Short Term Methylmercury Exposure on Growth and Development of the Large Yellow Croaker Embryos and Larvae - Yu, Xiang; Wu, Fangzhu; Xu, Xiaoqun; Chen, Quanzhen; Huang, Lin; Teklehaimanot Tesfai, Berhane; Cao, Liang; Xu, Xudan; Dou, Shuozeng; Huang, Wei (Frontiers in Marine Science, 2019)
The toxic effects of methylmercury (MeHg) on organisms have caused widespread concerns, but little has been reported on its effects in marine fish. This study investigated the acute and sub-lethal toxicities of MeHg chloride to large yellow croaker (Pseudosciaena crocea) embryos and larvae. Acute toxicity tests showed that the 48-h LC50 values of methylmercury to the embryos and larvae were 28.39 (21.33-33.98) and 18.27 (11.33-29.29) μg L -1 , respectively, while the 96-h LC50 value for larvae was 9.28 (4.41-14.49) μg L -1 , indicating that larvae were more sensitive to MeHg than the embryos. On the other hand, MeHg could cause low hatching success, increase larvae heart rate at concentrations ≥ 20 μg L -1 , as well as delayed hatching process, reduced survival and higher morphological malformations at concentrations ≥ 10 μg L -1 to the embryos and larvae. Results showed that the early life stages of large yellow croaker were sensitive to MeHg exposure.